KAZAKHSTAN-SAUDI ARABIA: FOREIGN POLICY CONTACTS AND INTERACTION IN THE CONTEXT OF ANTI-RUSSIAN SANCTIONS - KARABULATOVA, Alla; KIM, Leonid (CENTRAL ASIA AND THE CAUCASUS, 2017)
In the second decade of the twenty-first century, there has been an unprecedented increase in foreign economic activities driven by transnational corporations (TNCs). These entities are now key players as traders, investors, and promoters of advanced technologies, significantly influencing international labor migration. They have become pivotal in shaping the dynamics, structure, and competitiveness of global markets, as well as in the international movement of capital and the transfer of technological knowledge. Among the independent states in the Persian Gulf region, oil-rich monarchies have achieved substantial economic success. Over recent decades, the forces of globalization, expanding economic connections, and evolving international relations have propelled these Gulf states—who collectively control 43.9% of the world’s proven oil reserves and 15.5% of its natural gas resources—from the periphery to the center of global economics and Middle Eastern politics. Historically, the Middle East has been more of an object in geopolitical strategies rather than an active subject. Western perceptions have long held that despite its vast energy resources, the region struggles to develop efficient economic models and that local populations lack business acumen. However, this view has been challenged by recent developments. The Arabic Middle East, particularly through Saudi Arabia, has made significant advancements that have defied these Western stereotypes. Saudi Arabia, in particular, has become a major global investor, extending its economic influence well beyond the Middle East. Its investments now span various regions, including a notable alignment with Kazakhstan. This shift indicates a broader realignment in foreign policy priorities, reflecting the Gulf states' growing economic clout and their strategic reorientation on the global stage.